Financing European air defence through European Union debt - Armin Steinbach; Guntram B. Wolff (Bruegel, 2024)
Europe is vulnerable to air attacks by both state and non-state actors. Russia has substantially increased its production of hypersonic missiles, missiles and drones, while European air defence capacities remain patchy with little improvement in coverage in recent years. Air defence is a classic European public good. No individual nation alone can provide it comprehensively, while air defence provided individual European Union countries can offer significant benefits to Europe as a whole. Joint EU funding for the build-up of greater air defence capabilities would be thus justified and help ensure rapid and sufficient provisioning. Debt funding would be economically justified as air defence systems, such as Patriot and IRIS-T, involve large upfront costs - debt would allow the cost of the investment to be smoothed over longer periods. Issuing EU debt, similarly to what was done with the NextGenerationEU post-pandemic recovery instrument, would be justified given the level of the air-attack threat. EU debt funding of air defence system is legally possible. Debt funding for air defence would respect the EU's limited competence in defence and such a scheme would maintain the exceptional character of debt funding, with EU countries responding to a security threat in an act of solidarity. Joint debt issuance would not imply changing the command structure of air defence as foreseen under NATO and the European Sky Shield Initiative, but it would impact procurement processes. Procurement could be organised in the framework of the EU's existing Permanent Structured Cooperation (PESCO) system. Additional EU debt would benefit the development of European industrial capacities in air defence, even if in the short term some funds were used to buy systems from the United States. Significant funds for research and the development of the domestic industrial base should be part of the initiative.
Keywords: 330; security